The Manhattan Project - Stein, R. Conrad (Chicago : Childrens Press, 1993)
Recounts the history of the crash program that resulted in the development of the atomic bomb.
Booklist.
School Library Journal.
6.8
3-6
Keywords: Manhattan Project (U.S.) -- History -- Juvenile literature; Manhattan Project (U.S.); Manhattan Project (U.S.); Atomic bomb -- United States -- History -- Juvenile literature; Atomic bomb; Atomic bomb